E-Mentoring for Knowledge Sharing among Lecturers in Higher Technical Education Institutions: A Conceptual Framework - Marzuki, Mohammad Al Bukhari; Ishak, Rosnah (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2021)
A higher education institution serves as a centre for the creation, exchange, and sharing of information. Technical institutions play an important role in the creation and dissemination of technical knowledge to assist economic development. Experienced senior academics share their knowledge with newly appointed lecturers through a mentoring programme. The traditional mentoring relationship is a dynamic one in which a senior member of an institution or profession pays attention to a junior and provides professional and psychological aid. Because of technological advancements, HTEIs must use this chance to develop, share, and exchange knowledge regardless of time, space, or location through e-mentoring. E-mentoring is a revolutionary setting in which the mentoring interaction between the mentor and mentee is exclusively conducted online. The fundamental distinction between traditional mentoring and e-mentoring is the communication channel used. The e-mentoring concept is developed within the context of the HTEIs, using the Adult Learning Theory and the SECI Model. The concept's expected impact is measured using The Kammeyer-Mueller and Judge (2008) Framework, which describes the mentoring effect of a mentee in the mentoring programme. However, additional research is needed to assess the outcomes of e-mentoring, particularly in technical fields where face-to-face mentoring is favoured.